A generic tool for building fuzzy cognitive map systems - Papaioannou, Maria; Sofokleous, Anastasis A.; Neocleous, Costas (My University, 2010)
A generic system for simulating complex dynamical systems along the paradigm of fuzzy cognitive maps (FCM) has been created and tested. The proposed system enables a user to design appropriate FCM structures, by specifying the desired concepts and the various parameters such as sensitivities, as well as a variety of shaping functions. The user is able to see the results, change the parameters, modify the functions, and rerun the system using an alteration of the final results and make new conclusions. The system is introduced and demonstrated using a simple real case. The results of a usability test of the system suggest that the system is capable of simulating complicated FCM structures in an effective manner, helping the user to reduce the degree of risks during decision making
Keywords: Fuzzy systems; Dynamics; Soft computing; Large scale systems